Anxiety‐associated and separation distress‐associated behaviours in Angelman syndrome. Issue 10 (28th May 2019) - Wheeler, A. C.; Okoniewski, K. C.; Wylie, A.; DeRamus, M.; Hiruma, L. S.; Toth, D.; Christian, R. B.
Abstract: Background: Anxiety is considered a 'frequent' feature in the clinical criteria for Angelman syndrome; however, the nature and severity of anxiety symptoms have not been well characterised in this population. Anxiety behaviours, especially in response to separation from a preferred caregiver, have been described clinically but have not yet been explored empirically. Method: This study used a combination of standardised and clinician‐derived survey items to assess the frequency, nature and severity of behaviours associated with anxiety and separation distress in 100 individuals with Angelman syndrome. Family (e.g. income and maternal education) and individual (e.g. age, sex, genetic subtype, sleep difficulties and aggressive behaviours) variables were also gathered to assess possible predictors of higher anxiety levels. Approximately half of the sample was seen in clinic and assessed with standardised measures of development and daily functioning, allowing for an additional exploration of the association between anxiety symptoms and extent of cognitive impairment. Results: Anxiety concerns were reported in 40% of the sample, almost 70% were reported to have a preferred caregiver and over half displayed distress when separated from that caregiver. Individuals with the deletion subtype and individuals who are younger were less likely to have anxiety behaviours. Sleep difficulties and aggressive behaviour consistently significantly predicted total anxiety, the latter suggesting a need for future studies to tease apart differences between anxiety and aggression or anger in this population. Conclusions: Anxiety concerns, especially separation distress, are common in individuals with Angelman syndrome and represent an area of unmet need for this population.